Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.